Manufacturing method of laminates

JP2026165602AActive Publication Date: 2026-10-14TOYO INK MFG CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025058066
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14
Estimated Expiration
2045-03-31

AI Technical Summary

Benefits of technology

【0021】 本開示により、高速印刷適性が可能であり、細線再現性およびコーティング層除去性に優れ、品質管理が容易なフォトリソグラフィー法を使用せずにパターンを形成するパターン形成工程を含む積層体の製造方法及びそれに用いるコーティング剤を提供可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165602000001_ABST
    Figure 2026165602000001_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a laminate that includes a pattern formation step, which allows for high-speed printing, offers excellent fine line reproducibility and coating layer removal, and facilitates quality control, without using photolithography. [Solution] A method for manufacturing a laminate, comprising the steps of: printing a coating agent containing an aqueous resin and a colorant onto a substrate using a roll-to-roll method to form a patterned coating layer without using photolithography; forming a conductive film on the substrate on which the coating layer has been formed using a roll-to-roll method; and removing the coating layer by bringing the substrate on which the conductive film has been formed into contact with a coating layer removal liquid to form a conductive pattern.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for producing a laminate and a coating agent.

Background Art

[0002] Conventionally, lift-off methods and photolithography methods have been used as techniques for forming fine-patterned electrode layers on base materials of electronic components such as semiconductors and solar cell panels. Among these, from the perspective of improving productivity, the lift-off method (lift-off process), which does not require an etching step, has attracted attention.

[0003] In a typical lift-off process, (1) a resist layer is formed on a base material by attaching a photoresist film or applying a photoresist liquid. Next, (2) the resist layer is exposed using a photomask. Next, (3) an unnecessary resist layer is removed using a developer to form a resist pattern. Next, (4) an electrode layer is formed on the base material and the resist layer by sputtering or vapor deposition. Next, (5) the resist pattern can be removed to form an electrode pattern. However, this method has a large number of steps and has become a bottleneck in the production of semiconductors, solar cell panels and the like.

[0004] Accordingly, to improve productivity, processes that form a patterned resist layer by printing in the step (1) above and do not include the steps (2) and (3) above are being developed.

[0005] Patent Document 1 discloses a patterning method for a metal oxide film, which includes a step of pattern-printing a water-soluble resin on a synthetic resin film, a step of vapor-depositing a metal oxide over the entire pattern-printed surface of the synthetic resin film, and a step of washing the synthetic resin film with water to simultaneously remove the water-soluble pattern-printed portion and the metal oxide film vapor-deposited on its surface layer.

[0006] Patent Document 2 discloses a resist agent for the lift-off method used to form a resist film on a substrate when forming a conductive pattern on the substrate by the lift-off method, which contains hydroxyalkylcellulose in a proportion of 8 to 25% by mass.

[0007] Patent Document 3 discloses a method for manufacturing a substrate for a touch panel, which includes the steps of forming a transparent electrode on a transparent substrate and forming a metal electrode on the transparent substrate that conducts to the transparent electrode, wherein at least one of the transparent electrode and the metal electrode is formed by a lift-off method using a water-soluble resist agent containing at least one of a water-soluble polyester and hydroxyalkylcellulose. [Prior art documents] [Patent Documents]

[0008] [Patent Document 1] Japanese Patent Publication No. 2002-200833 [Patent Document 2] Japanese Patent Publication No. 2013-258215 [Patent Document 3] Japanese Patent Publication No. 2013-257669 [Overview of the project] [Problems that the invention aims to solve]

[0009] The technology disclosed in Patent Document 1 had several problems: it was difficult to remove the pattern by washing with water, the formation of fine-line printed patterns was poor, and it was difficult to visually confirm the formation state of the fine-line printed patterns, leading to quality control issues such as overlooking pattern formation defects.

[0010] The technologies disclosed in Patent Documents 2 and 3 provide resists suitable for screen printing. Such resists are suitable for printing on sheet-fed transparent substrates but not for high-speed printing because they require a long drying time after application. Thus, conventional methods, such as exposing the resist film to an aqueous resist removal solution to remove the resist film and the conductor on the resist film, have been considered unsuitable for continuous printing because they require a long time from application to drying of the resist.

[0011] This disclosure relates to a method for manufacturing a laminate, including a pattern forming step that forms a pattern without using photolithography, which enables high-speed printing, has excellent fine line reproducibility and coating layer removal properties, and facilitates quality control, and a coating agent used therein. [Means for solving the problem]

[0012] In other words, this disclosure is the following <1> ~ <8> Regarding.

[0013] <1> A process of forming a patterned coating layer on a substrate by printing a coating agent containing an aqueous resin and a colorant using a roll-to-roll method, without using photolithography. A step of forming a conductive film on a substrate on which the coating layer has been formed using a roll-to-roll method, and A method for manufacturing a laminate, comprising the step of contacting a substrate on which the conductive film is formed with a coating layer removal liquid to remove the coating layer and form a conductive pattern.

[0014] <2> The printing method is at least one selected from the group consisting of gravure printing, flexographic printing, waterless offset printing, inkjet printing, and screen printing. <1> A method for manufacturing the laminate described above.

[0015] <3> The thickness of the conductive film is 0.01 to 100 μm. <1> or <2> A method for manufacturing the laminate described above.

[0016] <4> The method for producing a laminate according to any one of <1> to <3>, wherein the thickness of the conductive film and the thickness of the coating layer satisfy the following formula. Formula 1 Thickness of conductive film [μm] < Thickness of coating layer [μm]

[0017] <5> The method for producing a laminate according to any one of <1> to <4>, wherein the colorant comprises at least one selected from the group consisting of organic pigments, inorganic pigments, and dyes.

[0018] <6> The method for producing a laminate according to any one of <1> to <5>, wherein the aqueous resin contained in the coating agent comprises an aqueous resin having a polar structure.

[0019] <7> The method for producing a laminate according to any one of <1> to <6>, wherein the coating layer removing liquid is water or an alkaline aqueous solution.

[0020] <8> A coating agent comprising an aqueous resin and a colorant, which is used in the production method according to any one of the above <1> to <7>. [Effects of the Invention]

[0021] According to the present disclosure, it is possible to provide a method for producing a laminate including a pattern forming step of forming a pattern without using a photolithography method that enables high-speed printability, is excellent in fine line reproducibility and coating layer removability, and facilitates quality control, and a coating agent used therefor. [Brief Description of the Drawings]

[0022] [Figure 1] This is a schematic diagram showing a state in which a coating agent is printed on a base material to form a patterned coating layer in a lift-off process. [Figure 2] This is a schematic diagram showing a state in which a conductive film is formed on the base material and the patterned coating layer shown in Fig. 1 in a lift-off process. [Figure 3]This is an illustrative diagram showing the state in which a conductive film has been formed on the substrate by removing the pattern coating layer shown in Figure 2 using a coating layer removal solution during the lift-off process. [Figure 4] This is a schematic cross-sectional view illustrating one embodiment of a printing system. [Modes for carrying out the invention]

[0023] The embodiments of this disclosure will be described in detail below, but the descriptions of embodiments or requirements described herein are examples of embodiments of this disclosure, and this disclosure can be modified to the extent that it solves the problem.

[0024] <Method for manufacturing laminates> One embodiment of the present disclosure relates to a method for manufacturing a laminate, comprising the steps of: printing a coating agent containing an aqueous resin and a colorant onto a substrate in a roll-to-roll manner to form a patterned coating layer without using photolithography; forming a conductive film on the substrate on which the coating layer has been formed in a roll-to-roll manner; and removing the coating layer by bringing the substrate on which the conductive film has been formed into contact with a coating layer removal liquid to form a conductive pattern.

[0025] The method for manufacturing a laminate according to this disclosure can be used in a lift-off process that forms a pattern without using photolithography. In this disclosure, the "lift-off process" is a step of removing a coating layer (resist film) made of a coating agent and forming a conductive pattern. The "lift-off process" is a process of forming and removing a resist film pattern using a known printing method such as gravure printing. In this disclosure, since the resist film pattern can be formed by printing, a photolithography step is unnecessary, and it is a process that differs from known technologies in which a photolithography step is essential.

[0026] An example of a lift-off process including a pattern formation step will be explained using Figures 1 to 3. The lift-off process including a pattern formation step includes, for example, forming a pattern coating layer 2 by gravure printing the coating agent of this disclosure onto areas on the substrate 1 where the conductive film 3 is not desired (Figure 1), then forming a conductive film 3 on the substrate 1 and the pattern coating layer 2 using an electrode material such as indium tin oxide by a method such as sputtering (Figure 2), and finally removing the pattern coating layer 2 using a coating layer removal solution described later. This makes it possible to form the conductive film 3 only where necessary (Figure 3).

[0027] Furthermore, the fine-line reproducibility evaluates whether or not there are any breaks in the fine lines of the final conductive pattern. By using the coating agent of this disclosure, the patterned coating layer described above can be formed with high precision, thereby suppressing breaks in the conductive pattern.

[0028] The method for manufacturing a laminate according to this disclosure can be used in a lift-off process that includes a pattern formation step for forming a pattern without using photolithography. For example, it is preferably used to form fine conductive patterns on a substrate of an electronic component used in the manufacture of a semiconductor or solar panel.

[0029] The following describes some embodiments of methods for manufacturing laminates. In some embodiments, the method for manufacturing a laminate is characterized by the following steps. (1) A process of forming a patterned coating layer on a substrate by printing a coating agent containing an aqueous resin and a coloring agent on the substrate using a roll-to-roll method without using photolithography. (2) A process of forming a conductive film on a substrate on which a coating layer has been formed using a roll-to-roll method. (3) A step of bringing a substrate on which a conductive film has been formed into contact with a coating layer removal solution to remove the coating layer and form a conductive pattern.

[0030] <Usage example> A laminate having a conductive pattern on a substrate can be used as part of a semiconductor or solar panel, for example, as the "substrate / transparent conductive film (-)" in a laminate configuration example of a perovskite solar cell: "substrate / transparent conductive film (-) / metal oxide layer / perovskite / hole transport layer / electrode (+)". It can also be used as a component in a battery management system such as an automotive battery.

[0031] <Roll-to-roll method> In some embodiments, the method for manufacturing the laminate involves performing the coating layer formation step and the conductive film formation step, respectively, using a roll-to-roll method. In one example of the roll-to-roll method, a long substrate is wound into a roll, the substrate is continuously transported from the roll-shaped substrate, a coating agent is printed on it, and after optional drying, the substrate is wound up to obtain a roll-shaped substrate with the coating layer formed. Next, the obtained roll-shaped substrate with the coating layer formed is further continuously transported to form a conductive film, and after optional drying, the substrate is wound up to obtain a roll-shaped substrate with the conductive film formed. Next, the roll-shaped substrate with the conductive film formed is further continuously transported to contact with a coating layer removal liquid to form a conductive pattern, and after optional drying, the substrate is wound up to obtain a roll-shaped substrate with the conductive pattern formed. In this example, roll winding is performed after each step of forming the coating layer, forming the conductive film, and removing the coating layer. However, roll winding may be performed after the processes from forming the coating layer to forming the conductive film are carried out continuously, or after the processes from forming the coating layer to removing the coating layer are carried out continuously, or roll winding may be performed after forming the coating layer, and then roll winding may be performed after the processes from forming the conductive film to removing the coating layer are carried out continuously. In other examples, the roll-shaped substrate may be cut into individual sheets before removing the coating layer, or the roll-shaped substrate may be cut into individual sheets after removing the coating layer.

[0032] According to some embodiments, the formation of the coating layer and the conductive film can be performed using a roll-to-roll method, enabling high-speed pattern formation of the conductive film. The coating agent contains an aqueous resin and a colorant, providing viscoelasticity suitable for high-speed printing, and enabling the formation of a highly detailed patterned coating layer even with a roll-to-roll method. Furthermore, the inclusion of an aqueous resin and a colorant in the coating agent ensures fine line reproducibility of the coating layer pattern. Therefore, even when the conductive film is subsequently formed using a roll-to-roll method, the reproducibility of the conductive pattern can be improved during the subsequent removal of the coating layer. Note that the manufacturing method described herein includes not only high-speed printing but also low-speed printing.

[0033] Furthermore, since the coating agent contains an aqueous resin and a colorant, the removal of the coating layer using a coating layer removal solution is enhanced, and together with the formation of a highly detailed patterned coating layer, fine line reproducibility of the conductive film can be obtained. In a preferred example, since the coating agent contains an aqueous resin having acidic groups and inorganic fine particles, the acidic groups of the aqueous resin adsorb to the surface of the colorant particles, forming a more stable colorant particle dispersion. As a result, the colorant particle dispersion has more suitable viscoelasticity, further improving high-speed printing suitability and fine line reproducibility. However, the above effects are based on scientific considerations, and this disclosure is not limited to embodiments that exhibit these effects.

[0034] For the reasons stated above, in some embodiments, the printing speed of the coating agent is preferably, for example, 10 m / min or more. High-speed printing of 25 m / min or more, 50 m / min or more, 100 m / min or more, or 120 m / min or more is also preferred. Furthermore, printing speeds of 250 m / min or less, 200 m / min or less, or 180 m / min or less are also preferred. In some embodiments, the coating agent can exhibit excellent fine line reproduction even in high-speed printing of 120 m / min or more in gravure printing, which is particularly productive.

[0035] <Base material> The substrate is not limited as long as it can form a coating layer and a conductive pattern. For example, in applications of next-generation solar cells, which have seen a surge in development in recent years toward realizing a decarbonized society, it is preferable to use a lightweight and flexible plastic film as the substrate. As plastic films, polyester films, polyimide films, polyamide films, and polyphenylene ethers (including polystyrene-modified ones) are preferred for their weather resistance. Examples of polyester films include polyethylene terephthalate (PET) and polyethylene naphthalate (PEN). To provide the laminate with water vapor barrier properties, the substrate itself may have a barrier layer such as a transparent vapor-deposited inorganic oxide layer, or a hard coat layer to prevent scratching. Furthermore, the substrate may have surface treatments such as corona treatment or flame treatment to provide easy adhesion for printing and post-processing, and may also have a coating layer.

[0036] <Formation of the coating layer> A patterned coating layer can be formed on a substrate by printing a coating agent containing an aqueous resin and a colorant on it using a roll-to-roll method. For example, the coating agent can be coated onto the substrate, and the volatile components can be removed to form the coating layer. Printing is preferred as the coating method. The printing method is preferably at least one selected from the group consisting of gravure printing, flexographic printing, waterless offset printing, inkjet printing, and screen printing. Among these, at least one selected from the group consisting of gravure printing, flexographic printing, waterless offset printing, and inkjet printing is preferred. Plate printing methods such as gravure printing, flexographic printing, waterless offset printing, and rotary screen printing are suitable for roll-to-roll printing using a rotary printing press. Plate printing allows for high-speed printing of multiple conductive patterns of the same shape in succession. Digital printing methods such as inkjet printing are also suitable for roll-to-roll printing using a rotary printing press. Among these, gravure printing and / or flexographic printing methods are particularly preferred, and gravure printing is even more preferred.

[0037] The coating agent is diluted with a diluent solvent to a viscosity and concentration suitable for gravure printing, and supplied to each printing unit, either alone or in mixtures, for application. The coating layer is then fixed by drying in an oven or the like.

[0038] The thickness of the coating layer is preferably 0.1 μm to 10 μm, more preferably 0.2 to 5 μm, even more preferably 0.3 to 3 μm, and particularly preferably 0.6 to 2 μm. When the thickness of the coating layer is within the above range, fine line reproducibility, cleanability, and fine line visibility tend to improve. It is preferable that the thickness of the conductive film [μm] < the thickness of the coating layer, and when this condition is met, the area of ​​the side surface of the pattern coating layer that is not covered by the conductive film increases, so the cleaning solution penetrates the coating layer more easily, and cleanability tends to improve. The printing speed is not particularly limited, but from the viewpoint of productivity, it is preferably 10 to 300 m / min, more preferably 50 to 200 m / min, and even more preferably 80 to 150 m / min.

[0039] In the process of printing the coating layer, volatile components such as solvents may be removed by drying the substrate after printing the coating agent. The drying temperature is preferably 70 to 120°C, and the drying time is preferably 0.1 to 10 seconds, more preferably 1 to 5 seconds. The airflow during drying is preferably 40 m / min or more. As the drying apparatus, a known continuous processing oven or an in-line oven attached to the printing press can be used, and it is preferable to use an in-line oven attached to the printing press.

[0040] Gravure printing (Gravure version) Gravure plates are cylindrical and made of metal. There are two methods for forming the cells of a gravure plate: engraving and etching (photosensitive film coating - exposure - development - etching). Etching is preferred because it allows cells to be formed along the edges of the image, resulting in sharper contours of the coating layer. Furthermore, the etching method allows for increased cell precision by improving the resolution during exposure. Suitable plate-making equipment includes, for example, the Sync Laboratory FXIII laser automatic plate-making system (laser drawing resolution: 3200 dpi in the longitudinal direction / 12800 dpi in the circumferential direction) or the MDC DIGILAS5000 laser plate-making and electronic engraving machine, with the MDC DIGILAS5000 being more preferable. In yet another example of the etching method, cells of the gravure plate may be formed by photosensitive film coating - laser irradiation - etching. Such plate-making equipment includes, for example, the MDC DIGILAS5000.

[0041] The line screen frequency, a parameter equivalent to the resolution during printing, is preferably 200 to 350 lines / inch. When the line screen frequency is 200 / inch or higher, the edge shape of the printed area tends to be better, which improves the reproduction and visibility of fine lines. When the line screen frequency is 350 / inch or lower, the cell openings become larger, which improves ink transfer, which also tends to improve the reproduction and visibility of fine lines.

[0042] The plate depth, a parameter that controls the amount of ink transferred, is preferably 15 to 25 μm. When the plate depth is 15 μm or more, streaking of the coating layer can be suppressed, which tends to improve fine line reproducibility and fine line visibility. When the plate depth is 25 μm or less, the amount of coating agent applied is appropriate, which suppresses bleeding of the coating layer, which tends to improve fine line reproducibility and fine line visibility. Furthermore, by setting the plate depth to 25 μm or less, the amount of coating agent applied can be reduced, which also reduces drying energy and improves printing speed, i.e., productivity. In addition, it is preferable that the plate has island patterns and, in addition to island patterns, printing frame processing, and when the line width of the frame processing is within the above range, fine line reproducibility and fine line visibility tend to improve.

[0043] In the case of water-based inks with slow drying times or polyester films with good wetting and spreading properties, the pattern line width of the printed material tends to be wider than the plate pattern line width due to the coating agent wetting and spreading on the film. In such cases, from the viewpoint of suppressing bleeding due to the wetting and spreading of the coating layer, the ratio of the plate pattern line width to the target pattern line width (plate pattern line width / target pattern line width) is preferably 75-90%, and more preferably 77-85%. When the plate pattern line width / target pattern line width is within the above range, fine line reproduction and fine line visibility are good.

[0044] (Gravure printing machine) In a gravure printing press, each printing unit is equipped with the above-mentioned gravure plate and doctor blade. There are multiple printing units, and typically, printing units corresponding to organic solvent-based printing inks and pattern inks can be configured, and each unit has an oven drying unit. Printing is performed by rotary printing using a roll printing method. The type of plate and doctor blade can be selected as appropriate, according to the specifications. In some embodiments, a coating layer pattern can be printed using a printing unit on the upstream side in the transport direction, and a conductive film can be formed using a conductive film forming unit on the downstream side in the transport direction.

[0045] <Flexographic printing> (Flexographic version) The flexographic plates used in the flexographic printing method of this embodiment include photosensitive resin plates that utilize ultraviolet curing or elastomer material plates that use a direct laser engraving method. From the viewpoint of fine line reproduction and fine line visibility, regardless of the method of forming the image portion of the flexographic plate, a screening screen count of 75 lines / inch or higher is preferred. Photosensitive resin plates are preferred for obtaining high-definition printed materials. Photosensitive resin plates include liquid plates that form a relief by curing a fluid liquid resin, and solid plates that form a relief by exposing and curing a sheet-like solid resin and removing unnecessary parts with a development process. Furthermore, solid plates have differences in various development processes, including solvent development types that use organic solvents, water development types that develop with an aqueous developer instead of an organic solvent, and thermal development types that absorb uncured parts with a nonwoven fabric by applying heat. Among these, the water development type is preferred because it produces a high-definition plate with less swelling. For processing the flexographic plate, a microcell and flat top are preferred. Microcell processing involves adding fine patterns to the printing plate to improve transferability and suppress unevenness and margins. Flat top processing blocks oxygen during exposure, resulting in a flat surface. Compared to round top processing, it tends to reduce dot gain during long runs, distributes pressure for increased plate durability, allows for kiss-touch printing, and minimizes the appearance of raised edges. The sleeves and cushioning tapes used to attach the printing plate can be selected as desired.

[0046] (Flexographic printing press) In a flexographic printing press, the anilox roller first receives the coating agent from the coating agent tank, and then the ink is transferred to the flexographic plate. The flexographic plate has the design to be printed embossed on it, and ink remains only on the design area. As the substrate passes between the impression cylinder and the flexographic plate, the design is transferred onto the substrate. The anilox roller has a fine cell structure, which allows for a uniform supply of the coating agent to the plate. The flexographic printing press used in this embodiment of the flexographic printing method can be a CI-type multi-color flexographic printing press, a unit-type multi-color flexographic printing press, etc., and the ink supply method can be a chamber method or a two-roll method. The anilox roll used in this embodiment of the flexographic printing method can be a cell-engraved ceramic anilox roll, a chrome-plated anilox roll, etc. To obtain a printed material with excellent dot reproducibility, an anilox roll with a line screen count of 5 times or more, preferably 6 times or more, the line screen count of the printing plate used during printing is used. For example, if the screen resolution is 75 lpi, an anilox roll of 375 lpi or higher is required, and if the screen resolution is 150 lpi, an anilox roll of 750 lpi or higher is required. Regarding the anilox roll capacity, from the perspective of fine line reproducibility and fine line visibility, it should be 1-8 cc / m². 2 Capacity, preferably 2-6 cc / m³ 2 This is an anilox roll.

[0047] <Waterless offset printing> (Waterless offset printing version) The waterless offset printing plate has a thin silicone layer on its surface. This silicone layer prevents the coating agent from adhering to the non-image areas. Beneath the silicone layer is an exposable polymer layer, which is the area where the image is formed. During plate making, this polymer layer is exposed to form the image area. The silicone layer and polymer layer are provided on an aluminum substrate, thereby providing a stable structure and durability. From the viewpoint of fine line reproduction and fine line visibility, the resolution of the waterless offset printing plate is preferably 300 dots / inch or higher, more preferably 1000 dots / inch or higher, and even more preferably 2000 dots / inch or higher.

[0048] (Waterless offset printing press) In a waterless offset printing press, all components except the printing plate can be the same as those used in conventional offset printing presses. For example, a coating agent is transferred to the plate via an ink roller, and only the image portion receives the coating agent, which is then transferred to the substrate in a later process. The image is transferred from the coated plate to a rubber cylinder called a blanket cylinder, and finally the ink is transferred from the blanket cylinder to the substrate. A web printing system is preferred for waterless offset printing presses, and a web printing system with a drying oven is more preferred.

[0049] <Screen Printing> (Screen print version) In screen printing, a design is transferred to a mesh material called a screen, which can then be used as a printing plate. Typically, synthetic fibers such as nylon or polyester, or metal materials, are used for the screen material. The screen has areas that the coating agent can pass through and areas that it cannot. The design can be printed by pressing the coating agent onto the substrate through the mesh. Low-density mesh is used in normal screen printing, but for high-definition printing, a higher-density mesh (more fibers and finer) is used, and from the viewpoint of fine line reproduction and fine line visibility, a mesh count of 200 or more is preferable.

[0050] (Screen printing machine) The screen printing apparatus supplies a coating agent onto the screen and uses a squeegee to spread the coating agent evenly. This allows the coating agent to pass through the openings in the screen and be transferred to the substrate. Among screen printing devices, rotary screen printing is preferred from the standpoint of productivity. Rotary screen printing uses a cylindrical screen. The coating agent is supplied into the screen, and as the screen rotates, the coating agent is pushed out from the mesh portion by a squeegee and transferred onto the substrate.

[0051] <Inkjet printing> In inkjet printing, two main technologies, the piezoelectric method or the thermal method, are used to spray the coating agent from the nozzle. The higher the nozzle density, the more ink drops can be accurately placed at once. Therefore, from the viewpoint of fine line reproduction and fine line visibility, a nozzle density of dots / inch or higher is preferable, 300 dots / inch is more preferable, and 600 dots / inch or higher is even preferable. Also, the smaller the nozzle diameter, the finer the drops that are formed. Therefore, from the viewpoint of fine line reproduction and fine line visibility, a nozzle diameter of 10 to 30 μm is preferable, and 15 to 20 μm is more preferable.

[0052] <Formation of conductive film> Conductive films can be formed by depositing a conductor onto a substrate using dry methods such as vapor deposition and sputtering. Among these methods, sputtering is preferred as it is excellent for depositing large-area films suitable for mass production. Examples of conductors include metals such as Al, Ti, Pb, Ni, Cu, Ag, Au, Cr, Sn, and In, and oxides such as ITO, FTO (fluorine-doped tin oxide), IZO, Al2O3, and SiO2. For applications in next-generation solar cells, ITO is particularly preferred because it is a transparent electrode and Pb-free. Conductive films can also be formed by laminating foil-shaped conductive films.

[0053] The conductive film can be formed using a roll-to-roll method, as described above for printing the coating layer. For example, in a rotary printing press, a printing unit can be provided on the upstream side in the transport direction to print the pattern of the coating layer, and a sputtering unit or deposition unit can be provided on the downstream side in the transport direction to form the conductive film. Since the conductive film only needs to be formed uniformly on the substrate and the coating layer, a high-resolution printing method is not required, and it is preferable to form it by sputtering, vacuum deposition, ion plating, or CVD (chemical vapor deposition).

[0054] The thickness of the conductive film is preferably 0.01 μm to 100 μm, more preferably 0.05 to 50 μm, and even more preferably 0.1 to 10 μm. From the viewpoint of coating layer removalability, the thickness of the conductive film is preferably 0.01 μm or more, and less than 10 μm, less than 5 μm, less than 1 μm, or less than 0.4 μm.

[0055] The thickness of the conductive film and the thickness of the coating layer preferably satisfy the following formula. This makes it even easier to remove the coating layer. Formula: Thickness of conductive film [μm] < Thickness of coating layer [μm]

[0056] For example, if the thickness of the coating layer is 100%, the thickness of the conductive film should be 0.1% or more, and preferably less than 100%, less than 50%, less than 10%, or less than 4%.

[0057] In this disclosure, the method for measuring the thickness of the coating layer involves sampling a 5mm x 25mm sample from a laminate having a patterned coating layer on a substrate, fixing it in a vise between plastic plates, creating a smooth cross-section using a retratome REM-710 (Yamato Koki Kogyo Co., Ltd.), measuring the surface at 10 points using a laser microscope VK-9700 (Keyence Corporation), and calculating the average value to obtain the thickness of the coating layer.

[0058] In this disclosure, the method for measuring the thickness of a conductive film involves sampling a 5 mm x 25 mm sample from a laminate having a pattern coating layer and a conductive layer on a substrate, fixing it in a vise between plastic plates, creating a smooth cross-section using a retratem REM-710 (Yamato Koki Kogyo Co., Ltd.), measuring 10 locations where the conductive layer is present using an electron microscope JSM-7800 (manufactured by JEOL Ltd.), and calculating the average value of these measurements to obtain the thickness of the conductive layer.

[0059] <Removal of the coating layer> The coating layer is brought into contact with the coating removal solution by an appropriate method. For example, the coating layer is brought into contact with the coating removal solution by spraying it onto the conductor covering the coating layer, or by immersing the coating layer and the conductor covering it in the coating removal solution. Immersion in the coating removal solution is preferred as a method for removing the coating layer.

[0060] The coating layer may be removed in-line after the conductive film is formed, or it may be removed by unwinding the rolled material. Removing the coating layer in-line after the conductive film is formed tends to improve fine wire reproducibility because the pressure applied during winding is eliminated. Additionally, it has the advantage of preventing blocking of the coating layer.

[0061] <Coating layer removal solution> As the coating layer removal liquid, it is preferable to use water from an environmental standpoint, such as facilitating wastewater treatment. Furthermore, the coating layer removal liquid can be a mixed solution containing a water-soluble organic solvent. Examples of water-soluble organic solvents include alcohols such as methanol, ethanol, 2-propanol, and 1,2-propanediol; glycol ethers such as ethylene glycol monomethyl ether, propylene glycol monomethyl ether, ethyl cellosolve, propylene glycol monopropyl ether, propylene glycol monoisopropyl ether, butyl cellosolve, ethylene glycol monoisobutyl ether, propylene glycol monobutyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, and dipropylene glycol monomethyl ether; and cyclohexanone.

[0062] Furthermore, the coating layer removal solution preferably contains at least one surfactant selected from the group consisting of nonionic surfactants, anionic surfactants, and cationic surfactants. When using a mixture of the above solvents, the water content in the mixture is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more, based on 100% by mass of the mixture. When the water content in the mixture is within the above range, the fine line reproducibility tends to improve.

[0063] Another embodiment of the coating layer removal solution is a lift-off process that forms a pattern without using photolithography. For example, when using a substrate from which the coating layer is difficult to remove with water alone, alkaline water can be used as the coating layer removal solution. Examples of alkaline water include aqueous solutions of inorganic bases such as potassium hydroxide and sodium hydroxide. The concentration of the alkaline water is not particularly limited as long as the coating layer can be removed, but is preferably 0.01 to 1% by mass, and more preferably 0.02 to 0.5% by mass. A surfactant can be used in combination with the alkaline water.

[0064] An example of a printing system will be described below using drawings. Figure 4 is a schematic cross-sectional view showing an example of a printing system. The printing system comprises, in order from the direction in which the substrate is transported, a substrate supply unit 10, a coating agent printing unit 20, a conductive film forming unit 30, and a substrate discharge unit 40. The substrate supply unit 10 houses a substrate roll 101 in which a long substrate 102 is wound into a roll shape, and continuously supplies the substrate 102 from the substrate roll 101. The substrate discharge unit 40 houses a substrate roll 401 in which a long substrate 104 is wound into a roll shape after printing.

[0065] The coating agent printing unit 20 is a rotary printing press that performs gravure printing on a long substrate 102. The coating agent printing unit 20 comprises a gravure cylinder 21a, an impression cylinder 21b, an ink pan 21c, and a doctor blade 21d. A pattern-shaped plate is formed on the outer surface of the gravure cylinder 21a, and the gravure cylinder 21a is pressurized by the impression cylinder 21b via the substrate 101, and the coating agent is contained in the ink pan 21c. As the gravure cylinder 21a rotates, the coating agent is carried from the ink pan 21c to the gravure cylinder 21a, the thickness of the coating agent is adjusted by the doctor blade 21d, and the coating agent is transferred to the substrate 102 by the pressure from the impression cylinder 21b to perform printing. After printing, the substrate may be dried in the drying unit 22.

[0066] The conductive film forming unit 30 receives a substrate on which a patterned coating layer has been formed, and uniformly forms a conductive film on the substrate and the coating layer. For example, the conductive film can be formed by sputtering 31.

[0067] The substrate on which the conductive film has been formed is wound up in the substrate discharge section 40. The substrate roll 401 after the conductive film has been formed is sent to a coating layer removal section (not shown). In the coating layer removal section, the coating layer removal liquid may be brought into contact with the long substrate while it is being transported, or the long substrate may be cut into sheets before being brought into contact with the coating layer removal liquid. Furthermore, the printing system is not limited to the example shown. For example, the coating layer printing section 20, the conductive film forming section 30, and the coating layer removal section may be performed continuously in a roll-to-roll manner, or each process may be performed in a roll-to-roll manner, wound up, and the wound substrate may be sent to the next process.

[0068] <Coating agent> The coating agent will be described below. In the manufacturing method of the laminate of this embodiment, the coating agent may contain an aqueous resin and a coloring agent. With this coating agent, good printability is obtained even in methods in which the substrate is transported at high speed, such as the roll-to-roll method, and the coating layer can be easily peeled off from the substrate after the conductive film has been formed.

[0069] <Water-based resin> The coating agent of this disclosure includes an aqueous resin. The aqueous resin is a resin that is soluble in an aqueous medium, and preferably a resin that is soluble in an aqueous coating layer removal solution. For example, the aqueous resin may be a resin that is miscible with an aqueous solvent, as described later.

[0070] The aqueous resin may contain an aqueous resin having a polar structure. Examples of aqueous resins having a polar structure include aqueous resins having polar groups and aqueous resins having polar moieties in the resin skeleton. Examples of polar groups and polar moieties include one or more selected from the group consisting of acid groups, hydroxyl groups, ether bonds, ester bonds, urethane bonds, amino groups, and amide groups. The resin skeleton is preferably one of the aqueous resins having acidic groups described later. For example, at least one selected from the group consisting of polyvinyl alcohol resins, acrylic resins, urethane resins, polysaccharide resins, casein, polyether resins, polyester resins, polyethyleneimine resins, polyallylamine resins, and polyvinylpyrrolidone resins. Among these, one or more selected from the group consisting of polyvinyl alcohol resins, acrylic resins, urethane resins, casein, polyether resins, polyethyleneimine resins, polyallylamine resins, and polyvinylpyrrolidone resins is preferred. Water-based resins with a polar structure are less prone to gelation and maintain an appropriate viscosity range, making them suitable for high-speed printing of coatings. This allows for high-resolution printing of coating layer patterns and further enhances the fine-line reproducibility of conductive films. Examples of polysaccharide-based resins include cellulose resins.

[0071] <Water-based resin containing acidic groups> In some embodiments, the aqueous resin is preferably an aqueous resin having an acidic group, and a combination of an aqueous resin having an acidic group and an aqueous resin not having an acidic group may be used. Examples of acidic groups include sulfonic acid groups, carboxyl groups, and phenolic hydroxyl groups. Among these, carboxyl groups are preferred. The presence of an acidic group in the aqueous resin provides adsorption capacity to the colorant. The acid value of the aqueous resin having an acidic group is preferably 5 to 200 mg KOH / g, and more preferably 30 to 150 mg KOH / g. When the acid value of the aqueous resin having an acidic group is within the above range, fine wire reproducibility and immersion cleaning performance tend to improve.

[0072] Examples of aqueous resin skeletons having acidic groups include polyvinyl alcohol resins, acrylic resins, styrene-acrylic resins, styrene-maleic acid resins, urethane resins, polylactic acid resins, resol-type phenolic resins, methylolated urea resins, methylolated melamine resins, polyethylene oxide, polyacrylamide, polysaccharide resins, and modified resins thereof. These aqueous resins having acidic groups can be used individually or in combination of two or more. Among the above, one or more selected from the group consisting of polyvinyl alcohol resins, acrylic resins, and polysaccharide resins are preferred, polyvinyl alcohol resins and / or polysaccharide resins are more preferred, and polyvinyl alcohol resins are even more preferred. The polysaccharide resin can be any compound in which two or more known monosaccharides are bonded together, such as cellulose resins, pullulan, starch, agarose, and gum arabic. Among these, it is preferable that it be one or more selected from the group consisting of cellulose resins, pullulan, and starch. Furthermore, in the case of resin skeletons that do not have acidic groups, acidic groups can be imparted by acid modification using known methods.

[0073] Polyvinyl alcohol-based resins tend to thicken in aqueous solutions, making them difficult to remove when washing with water. However, combining them with colorants can improve the efficiency of removal during water washing. Furthermore, the presence of acidic groups in the polyvinyl alcohol-based resin stabilizes the dispersibility of colorants and inorganic fine particles through the action of the acidic groups, and also increases solubility in water, thereby improving washability during water washing. Polysaccharide-based resins also tend to thicken in aqueous solutions, but by combining them with colorants, and preferably by including acidic groups in the polysaccharide-based resin, the dispersibility of colorants, especially inorganic fine particles, and washability during water washing can be improved. Carboxymethylcellulose (CMC) can be preferably used as a polysaccharide-based resin having acidic groups. Carboxymethylcellulose can improve the dispersibility of colorants, especially inorganic fine particles. From the viewpoint of suppressing thickening and improving washability with water, it is preferable that the degree of etherification of carboxymethylcellulose be 0.5 or higher, 0.6 or higher, or 0.7 or higher. Within these ranges, even with influences from environmental factors such as temperature and pH, it is possible to suppress the thickening of carboxymethylcellulose and improve its washability with water.

[0074] From the viewpoint of fine line reproducibility, immersion washability, suitability for high-speed printing, and stability over time, the content of the aqueous resin having an acidic group is preferably 3 to 70% by mass, more preferably 5 to 50% by mass, and even more preferably 10 to 30% by mass, based on 100% by mass of the nonvolatile content of the coating agent.

[0075] <Polyvinyl alcohol-based resin (A)> As described above, the aqueous resin having an acidic group is preferably a polyvinyl alcohol-based resin (A) having an acidic group. The polyvinyl alcohol-based resin (A) may be any resin having the above-mentioned acidic group and vinyl alcohol units, and may also be an ethylene vinyl alcohol resin containing ethylene-derived structural units.

[0076] The degree of polymerization of the polyvinyl alcohol-based resin (A) is preferably 100 to 3,000, and more preferably 500 to 2,400. When the degree of polymerization of the polyvinyl alcohol-based resin (A) is within the above range, the immersion washability, fine line reproducibility, high-speed printing suitability, and long-term stability are good.

[0077] The content of ethylene-derived structural units in the polyvinyl alcohol-based resin (A) is preferably 1 to 40 mol%, more preferably 3 to 20 mol%, and even more preferably 5 to 15 mol%. When the content of ethylene-derived structural units is within the above range, the immersion washability and long-term stability are good.

[0078] The polyvinyl alcohol-based resin (A) can be a resin that has been crosslinked with a crosslinking agent. Examples of known crosslinking agents include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, melamine-based crosslinking agents, oxazoline-based crosslinking agents, and silane coupling-based crosslinking agents, with oxazoline-based crosslinking agents and / or silane coupling-based crosslinking agents being preferred.

[0079] The degree of saponification of the polyvinyl alcohol-based resin (A) is expressed by the following formula (Formula 2), and is preferably 80 mol% or more, more preferably 90 mol% or more, and preferably 95 mol% or more. When the degree of saponification of the polyvinyl alcohol-based resin (A) is within the above range, the immersion washability and long-term stability are good. (Equation 2) Degree of saponification: (Number of hydroxyl groups) / {(Number of hydroxyl groups) + (Number of acetate groups)} × 100 [mol%]

[0080] Examples of commercially available polyvinyl alcohol-based resins (A) include Kuraray Poval 25-88KL (manufactured by Kuraray Co., Ltd., itaconic acid-modified polyvinyl alcohol resin), 6-77KL (manufactured by Kuraray Co., Ltd., acid-modified polyvinyl alcohol resin), Gosenex L-3266, and CKS-50 (manufactured by Mitsubishi Chemical Corporation, sulfonic acid-modified polyvinyl alcohol resin).

[0081] <Water-based resin without acidic groups> In some embodiments, the coating agent may include an aqueous resin that does not have acidic groups. The aqueous resin that does not have acidic groups may be used alone or in combination with an aqueous resin that has acidic groups. Examples of aqueous resins that do not have acidic groups include polyvinyl alcohol-based resins, acrylic resins, styrene-acrylic resins, styrene-maleic acid resins, urethane resins, polylactic acid resins, polysaccharide-based resins, and modified resins thereof. These hydrophilic resins can be used individually or in combination of two or more. Among the above, it is preferable to include a polyvinyl alcohol-based resin.

[0082] From the viewpoint of fine line reproducibility, suitability for high-speed printing, and ease of immersion cleaning, the content of the aqueous resin without acidic groups is preferably 0.1 to 30% by mass, more preferably 1 to 15% by mass, and even more preferably 2 to 8% by mass, based on 100% by mass of the coating agent.

[0083] In some embodiments, the total content of the aqueous resin in the coating agent is preferably 10 to 80% by mass, more preferably 25 to 70% by mass, and even more preferably 40 to 60% by mass, based on 100% by mass of the non-volatile content of the coating agent, from the viewpoint of fine line reproducibility, immersion washability, suitability for high-speed printing, and stability over time. By having a total content of 20% by mass or less, 18% by mass or less, or 15% by mass or less, the dispersibility when using colorants, especially inorganic fine particles, and the washability with water can be further improved. Furthermore, the coating agent can be made low viscosity while maintaining the dispersibility when using colorants, especially inorganic fine particles, and can have viscoelastic properties suitable for high-speed printing.

[0084] In some embodiments, when the coating agent includes an aqueous resin having an acidic group and an aqueous resin not having an acidic group, the mass ratio of the aqueous resin having an acidic group to the aqueous resin not having an acidic group is preferably 9:1 to 1:9, and more preferably 7:3 to 3:7. When the mass ratio is within the above range, fine line reproducibility, immersion washability, suitability for high-speed printing, and stability over time are good.

[0085] <Polyvinyl alcohol-based resin (B)> As described above, in some embodiments, the coating agent may also preferably include a polyvinyl alcohol-based resin (B) that does not have acidic groups. This polyvinyl alcohol-based resin (B) that does not have acidic groups is preferably included in the coating agent together with an aqueous resin that has acidic groups. The polyvinyl alcohol-based resin (B) may be any resin that does not have acidic groups and has vinyl alcohol units, and may further contain ethylene-derived structural units. For example, it may be an ethylene vinyl alcohol resin. Preferred embodiments of the degree of polymerization, crosslinking, and saponification of the polyvinyl alcohol-based resin (B) can be found by referring to the description of <polyvinyl alcohol-based resin (A)> above.

[0086] The polyvinyl alcohol-based resin (B) preferably contains ethylene-derived structural units, and the content of ethylene-derived structural units in the polyvinyl alcohol-based resin (B) is preferably 1 to 40 mol%, more preferably 3 to 20 mol%, and even more preferably 5 to 15 mol%. When the content of ethylene-derived structural units is within the above range, the immersion washability and long-term stability are good.

[0087] <Coloring agent> In some embodiments, the colorants include organic or inorganic pigments and dyes. Pigments with high color development and heat resistance are preferred, and organic pigments are generally preferred. The colorants may be used individually or in combination of two or more. Pigments are preferred, and inorganic pigments are more preferred, from the viewpoint of viscoelasticity suitable for high-speed printing. Furthermore, organic or inorganic pigments and dyes are preferred from the viewpoint of fine line visibility.

[0088] <Pigments> The average particle diameter (D50), which is the particle diameter at 50% of the cumulative value in the volume-based particle size distribution measured by laser diffraction / scattering of the pigment, is preferably 5 μm or less, more preferably 2 μm or less, even more preferably 1 μm or less, particularly preferably 0.5 μm or less, and most preferably 0.01 to 0.1 μm. When the average particle diameter measured by laser scattering of the pigment is within the above range, fine line reproducibility, suitability for high-speed printing, and stability over time are improved.

[0089] The specific surface area of ​​the pigment is 10 to 100 m². 2 / g is preferred, 10-80m 2 It is more preferable that the specific surface area of ​​the pigment is within the above range. When the specific surface area of ​​the pigment is within the above range, fine line reproducibility, suitability for high-speed printing, and stability over time are improved.

[0090] The pigment may be in known shapes such as spherical, square, cubic, or layered, but from the viewpoint of dispersibility, it is preferably spherical. When the pigment is spherical, fine line reproduction, immersion washability, suitability for high-speed printing, and stability over time are improved.

[0091] The following are specific examples of organic pigments, indicated by their color index numbers. Red pigments include, for example, CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 12, 14, 15, 16, 17, 21, 22, 23, 31, 32, 37, 38, 41, 47, 48, 48:1, 48:2, 48:3, 48:4, 49, 49:1, 49:2, 50:1, 52:1, 52:2, 53, 53:1, 53:2, 53:3, 57, 57:1, 57:2 , 58:4, 60, 63, 63:1, 63:2, 64, 64:1, 68, 69, 81, 81:1, 81:2, 81:3, 81:4, 83, 88, 90:1, 101, 101:1, 104, 108, 108:1, 109, 112, 113, 114, 122, 123, 144, 146, 147, 149, 151, 166, 168, 169, 170, 172, 173, 174, 175, 176, 177, 178, 179, 181, 184, 185, 187, 188, 190, 193, 194, 200, 202, 206, 207, 208, 209, 210, 214, 216, 220, 221, 224, 230, 231, 232, 233, 235, 236, 237, 238, 239, 242, 243, 245, 247, 249, 2 Examples include 50, 251, 253, 254, 255, 256, 257, 258, 259, 260, 262, 263, 264, 265, 266, 267, 268, 269, 270, 271, 272, 273, 274, 275, 276, 277, 278, 279, 280, 281, 282, 283, 284, 285, 286, 287, 291, 295, 296, etc.

[0092] Examples of blue pigments include CI Pigment Blue 1, 1:2, 9, 14, 15, 15:1, 15:2, 15:3, 15:4, 15:6, 16, 17, 19, 25, 27, 28, 29, 33, 35, 36, 56, 56:1, 60, 61, 61:1, 62, 63, 66, 67, 68, 71, 72, 73, 74, 75, 76, 78, and 79.

[0093] Examples of purple pigments include CI Pigment Violet 1, 1:1, 2, 2:2, 3, 3:1, 3:3, 5, 5:1, 14, 15, 16, 19, 23, 25, 27, 29, 31, 32, 37, 39, 42, 44, 47, 49, and 50.

[0094] Examples of green pigments include CI Pigment Green 1, 2, 4, 7, 8, 10, 13, 14, 15, 17, 18, 19, 26, 36, 37, 45, 48, 50, 51, 54, 55, 58, 59, 62, 63, etc.

[0095] Yellow pigments include, for example, CI Pigment Yellow 1, 2, 3, 4, 5, 6, 10, 12, 13, 14, 15, 16, 17, 18, 24, 31, 32, 34, 35, 35:1, 36, 36:1, 37, 37:1, 40, 42, 43, 53, 55, 60, 61, 62, 63, 65, 73, 74, 77, 81, 83, 93, 94, 95, 97, 98, 100, 101, 104, 106, 108, 109, 110, 113, 114, 115, 116, 117, 118 Examples include 119, 120, 123, 126, 127, 128, 129, 138, 139, 147, 150, 151, 152, 153, 154, 155, 156, 161, 162, 164, 166, 167, 168, 169, 170, 171, 172, 173, 174, 175, 176, 177, 179, 180, 181, 182, 185, 187, 188, 192, 193, 194, 196, 198, 199, 213, 214, 231, 233, etc.

[0096] Examples of orange pigments include CI Pigment Orange 36, 38, 43, 51, 55, 59, 61, 71, or 73.

[0097] Examples of cyan coloring compositions include blue pigments such as CI Pigment Blue 15:1, 15:2, 15:4, 15:3, 15:6, 16, and 81.

[0098] Examples of magenta colored compositions include purple pigments and red pigments such as CI Pigment Violet 1, 19, CI Pigment Red 144, 146, 177, 169, and 81.

[0099] Inorganic pigments include metal particles, metal oxide particles, metal carbonate particles, metal sulfide particles, non-metal oxide particles, mineral particles, and carbon black. Examples of inorganic pigments include calcium carbonate, titanium dioxide, barium sulfate, zinc oxide, lead sulfate, lead yellow, zinc yellow, red iron(III) oxide, cadmium red, ultramarine, Prussian blue, chromium oxide green, cobalt green, amber, and synthetic iron black. These pigments may be surface-treated with resins or the like. In addition, inorganic fine particles, as described later, may be used as inorganic pigments.

[0100] Examples of dyes include acid dyes, direct dyes, basic dyes, salt-forming dyes, oil-soluble dyes, disperse dyes, reactive dyes, mordant dyes, vat dyes, and sulfur dyes. Also included are derivatives of dyes and lake pigments, which are dyes that have been transformed into lakes.

[0101] The chemical structures of dyes include, for example, azo dyes, disazo dyes, azomethine dyes (indoaniline dyes, indophenol dyes, etc.), dipyromethene dyes, quinone dyes (benzoquinone dyes, naphthoquinone dyes, anthraquinone dyes, anthrapyridone dyes, etc.), carbonium dyes (diphenylmethane dyes, triphenylmethane dyes, xanthene dyes, acridine dyes, etc.), and quinoneimine dyes (oxazine dyes). Examples include dyes such as thiazine dyes, azine dyes, polymethine dyes (oxonol dyes, merocyanine dyes, allylidene dyes, styryl dyes, cyanine dyes, squarylium dyes, croconium dyes, etc.), quinophthalone dyes, phthalocyanine dyes, subphthalocyanine dyes, perinone dyes, indigo dyes, thioindigo dyes, quinoline dyes, nitro dyes, nitroso dyes, and rhodamine dyes. Among these, azo dyes, xanthene dyes, cyanine dyes, triphenylmethane dyes, anthraquinone dyes, dipyromethene dyes, squarylium dyes, quinophthalone dyes, phthalocyanine dyes, and subphthalocyanine dyes are preferred from the viewpoint of color characteristics such as hue, color separation, and color unevenness, with xanthene dyes, cyanine dyes, triphenylmethane dyes, anthraquinone dyes, dipyromethene dyes, and phthalocyanine dyes being more preferred. The specific structures of the dyes are described in "New Edition Dye Handbook" (edited by the Society of Synthetic Organic Chemistry; Maruzen, 1970), "Color Index" (The Society of Dyers and colourists), and "Pigment Handbook" (edited by Okawara et al.; Kodansha, 1986), among others.

[0102] The colorant content in the coating agent is preferably 3 to 70% by mass, more preferably 5 to 40% by mass, and even more preferably 10 to 25% by mass, based on 100% by mass of the non-volatile content of the coating agent. When the colorant content is within the above range, fine line reproducibility, immersion washability, suitability for high-speed printing, stability over time, and fine line visibility are improved. The improved stability over time of the coating agent allows for higher-resolution printing of the coating agent pattern, thus further improving the fine line reproducibility of the conductive pattern.

[0103] To improve the dispersibility of colorants, dispersants can be used. Examples of dispersants include surfactants and resin dispersants. Among these, resin-type dispersants are preferred, and the structures of resin-type dispersants are preferably AB block polymers, comb-type polymers, and graft polymers. Examples of resin types for resin-type dispersants include acrylic resins, styrene-acrylic resins, and polyester resins. Resin-type dispersants preferably contain one or more of acidic groups and amino groups, depending on the polarity of the colorant. The content of the dispersant is preferably 3 to 200 parts by mass, and more preferably 5 to 100 parts by mass, per 100 parts by mass of colorant.

[0104] The mass ratio of the aqueous resin to the colorant is preferably 1:0.01 to 1:3, more preferably 1:0.05 to 1:2, and even more preferably 1:0.1 to 1:1. When the mass ratio of the aqueous resin to the colorant is within the above range, fine line reproducibility, immersion washability, suitability for high-speed printing, stability over time, and fine line visibility are further improved.

[0105] <Inorganic fine particles> In some embodiments, the colorant preferably contains at least one inorganic pigment, and more preferably inorganic fine particles as one embodiment of the inorganic pigment. The inorganic fine particles are preferably particles that are finely ground to a degree that can be dispersed in the coating agent. The inorganic fine particles may be metal fine particles, alloy fine particles, and inorganic compound fine particles. The inorganic fine particles may be inorganic compound fine particles, and may contain at least one selected from the group consisting of inorganic oxide fine particles, inorganic carbonate fine particles, inorganic sulfate fine particles, and mineral fine particles. Examples of inorganic fine particles include titanium dioxide, zinc oxide, zinc sulfide, chromium oxide, aluminum particles, mica, bronze powder, chrome vermilion, lead yellow, cadmium yellow, cadmium red, ultramarine, Prussian blue, red iron oxide, yellow iron oxide, iron black, silica, barium sulfate, mica, montmorillonite, kaolin clay, talc, calcium carbonate, and magnesium carbonate. Preferably, at least one selected from the group consisting of calcium carbonate, barium sulfate, magnesium carbonate, silica, titanium dioxide, talc, montmorillonite, kaolin, and mica is used, with calcium carbonate being more preferable. The specific gravity of the inorganic fine particles is preferably 1.5 to 6, 2 to 4, or 2.4 to 2.7 from the viewpoint of suppressing sedimentation in the coating agent. Calcium carbonate is preferred because its specific gravity is low and it does not easily settle, thus improving the stability of the coating agent and reducing the increase in viscosity of the coating agent due to oil absorption and shape.

[0106] The pH of the extract water for inorganic fine particles is preferably neutral to alkaline, preferably 7.5 to 14, more preferably 7.8 to 12, and even more preferably 8.0 to 9.0. In particular, if the pH is alkaline, the acidic groups of the aqueous resin are easily adsorbed, which improves the fine wire reproducibility, immersion washing performance, and stability over time. The pH of the extract water for inorganic fine particles can be determined by mixing 5 parts inorganic fine particles with 100 parts ion-exchanged water, boiling for 5 minutes, stirring for 30 minutes, and then measuring the pH of the supernatant water with a pH meter in accordance with JIS Z 8802.

[0107] <Calcium carbonate> Calcium carbonate can be classified into natural calcium carbonate (heavy calcium carbonate) and synthetic calcium carbonate (light calcium carbonate). Natural calcium carbonate is produced directly from limestone, for example, by mechanically crushing and classifying raw limestone. Synthetic calcium carbonate is produced from calcium hydroxide, for example, by reacting calcium hydroxide with carbon dioxide. Calcium carbonate that has been further surface-treated with fatty acids, resin acids, silane coupling agents, etc., can also be used.

[0108] The inorganic fine particle content in the coating agent is preferably 3 to 20% by mass, and more preferably 5 to 15% by mass, based on 100% by mass of the coating agent. When the inorganic fine particle content is within the above range, fine line reproducibility, immersion washability, suitability for high-speed printing, and stability over time are improved.

[0109] The coating agent preferably contains an aqueous resin having an acidic group and inorganic fine particles. In this case, the mass ratio of the aqueous resin having an acidic group to the inorganic fine particles is preferably 1:0.2 to 1:3, and more preferably 1:0.8 to 1:2. When the mass ratio of the aqueous resin having an acidic group to the inorganic fine particles is within the above range, fine line reproducibility, immersion cleaning ability, suitability for high-speed printing, and stability over time are improved.

[0110] <Aqueous solvent> In some embodiments, the coating agent preferably contains an aqueous solvent. The main component of the aqueous solvent is preferably water, but in addition to water, a water-soluble organic solvent can be used. Specifically, depending on the printing method and printing conditions (speed, plate depth, design, drying temperature), it may contain an alcohol-based organic solvent, a glycol-based organic solvent, etc. Among these, it is preferable to include an alcohol-based organic solvent from the viewpoint of fine line reproducibility, suitability for high-speed printing, and long-term stability. In this disclosure, "water as the main component" means that water is the most abundant component in an aqueous solvent. Furthermore, a water-soluble organic solvent refers to a solvent that is liquid at 25°C and has a solubility of 1% by mass or more in water at 25°C.

[0111] From the viewpoint of fine line reproducibility, suitability for high-speed printing, and stability over time, the aqueous solvent content is preferably 50 to 95% by mass, and more preferably 70 to 90% by mass, of 100% by mass of the coating agent.

[0112] From the viewpoint of fine line reproducibility, suitability for high-speed printing, and stability over time, the water content is preferably 70 to 100% by mass, and more preferably 85 to 95% by mass, of 100% by mass of the aqueous solvent.

[0113] The content of water-soluble organic solvents such as alcohol-based organic solvents and glycol-based organic solvents is preferably 0.1 to 30% by mass, and more preferably 1 to 15% by mass, per 100% by mass of the coating agent, from the viewpoint of long-term stability, suitability for high-speed printing, and fine line reproduction.

[0114] Examples of the above-mentioned alcohol-based organic solvents include methanol, ethanol, n-propanol, isopropanol, isobutanol, n-butanol, tert-libutanol, hexanol, octanol, and decanol. In the case of coating methods using gravure printing or flexographic printing, at least one selected from the group consisting of methanol, ethanol, n-propanol, and isopropanol is preferred, with n-propanol being even more preferred in terms of stability.

[0115] When the aqueous solvent contains water and an alcohol-based organic solvent, the mass ratio of water to the alcohol-based organic solvent is preferably 70:30 to 97:3, and more preferably 85:15 to 95:5, from the viewpoint of long-term stability, suitability for high-speed printing, and fine line reproduction.

[0116] Examples of the glycol-based organic solvents mentioned above include acetylenediol, ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monooctyl ether, diethylene glycol, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, triethylene glycol, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monopropyl ether, triethylene glycol monobutyl ether, propylene glycol, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, dipropylene glycol, dipropylpropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol, tripropylene glycol monomethyl ether, tripropylene glycol monoethyl ether, tripropylene glycol monopropyl ether, tripropylene glycol monobutyl ether, and dibutyl glycol. In particular, at least one selected from the group consisting of diethylene glycol monoethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, and propylene glycol monopropyl ether is preferred, and propylene glycol and / or propylene glycol monopropyl ether is more preferred. These water-soluble organic solvents may be used individually or in combination of two or more.

[0117] When the aqueous solvent contains water and a glycol-based organic solvent, the mass ratio of water to the glycol-based organic solvent is preferably 100:10 to 100:0.2, and more preferably 100:5 to 100:0.2. When the mass ratio of water to the glycol-based organic solvent is within the above range, fine line reproducibility, suitability for high-speed printing, and stability over time are improved.

[0118] <Additives> In some embodiments, the coating agent may include known additives such as isocyanate compounds, silane coupling agents, dispersants, stabilizers, viscosity modifiers, and colorants, as long as they do not impair the effects of the present disclosure.

[0119] Another embodiment of the manufacturing method for the laminate is an alkali-removable coating agent that uses Al-Ali water as the coating layer removal solution. Alkali-removable coating agents are particularly useful in lift-off processes that form patterns without using photolithography, for example, when using substrates from which the coating layer is difficult to remove with water alone.

[0120] <Alkaline-removable coating agent> The alkali-removable coating agent may contain an alkali-soluble resin and a coloring agent. The alkali-removable coating agent may be the same as or different from the <coating agent> described above. The alkali-soluble resin is a resin having one or more acidic groups selected from the group consisting of sulfonic acid groups and carboxyl groups.

[0121] The alkali-soluble resins can be, for example, polyvinyl alcohol, urethane resin, styrene-acrylic resin, styrene (anhydrous) maleic acid resin, acrylic resin, acrylamide resin, or acrylic / acrylamide copolymer resin. From the viewpoint of fine line reproducibility and removeability, urethane resin, acrylic resin, styrene-acrylic resin, and styrene (anhydrous) maleic acid resin are preferred.

[0122] The acid value of the alkali-soluble resin is preferably 30 to 200 mg KOH / g, and more preferably 60 to 150 mg KOH / g. When the resin has an appropriate acid value, the removalability of the coating layer is improved. The content of the alkali-soluble resin is preferably 1 to 95% by mass, and more preferably 5 to 80% by mass, of the non-volatile content of the alkali-removable coating agent.

[0123] The weight-average molecular weight (Mw) of the alkali-soluble resin is preferably 2,000 to 200,000, and more preferably 3,000 to 150,000. When the resin has an appropriate Mw, it can achieve a high degree of both fine-wire formation and alkali-release properties. Note that Mw is the molecular weight on a polystyrene basis, measured by gel permeation chromatography.

[0124] The particles contained in the alkali-removable coating agent include resin particles, colorants, and inorganic fine particles. The mass ratio of alkali-soluble resin and particles is the same as described above.

[0125] <Method of manufacturing coating agent> In some embodiments, the coating agent can be manufactured by mixing, for example, an aqueous resin, a colorant, and optionally an aqueous solvent, dispersing the colorant using a disperser, and then mixing various additives and organic solvents into the resulting dispersion. Commonly used dispersers such as roller mills, ball mills, pebble mills, attritors, and sand mills can be used.

[0126] In some embodiments, the viscosity of the coating agent, measured according to JIS K7117-1 at 25°C and with a non-volatile content of 18% by mass, is preferably 20 to 450 mPa·s, more preferably 100 to 300 mPa·s, and even more preferably 200 to 280 mPa·s. When the viscosity of the coating agent at 25°C and with a non-volatile content of 18% by mass is within the above range, viscosity adjustment for printing, etc., with a dilution solvent is possible while maintaining the necessary non-volatile content, resulting in good fine line reproducibility, suitability for high-speed printing, and stability over time. Furthermore, from the viewpoint of suitable viscosity for high-speed gravure printing and flexographic printing, the viscosity at 25°C and with a non-volatile content of 10% is preferably 20 to 200 mPa·s, and more preferably 50 to 150 mPa·s. When the viscosity of the coating agent at 25°C and with a non-volatile content of 10% by mass is within the above range, fine line reproducibility and suitability for high-speed printing are good.

[0127] <Residual rate of the coating layer> In this disclosure, the residual rate of the coating layer is the value represented by (Formula 1) below after processing a laminate, which has been coated with a coating agent on a substrate to form a coating layer with a thickness of 1 μm, under the following conditions. The residual rate of the coating layer is preferably less than 80% by mass, more preferably less than 50% by mass, even more preferably less than 10% by mass, and particularly preferably less than 5% by mass. When the residual rate of the coating layer is within the above range, the removal rate of the coating layer and unnecessary conductive film portions is improved during immersion cleaning, and thus the fine line reproducibility tends to improve. (Processing conditions) The laminate was immersed in deionized water at 40°C for 10 minutes, then dried in an oven at 80°C for 1 minute. (Equation 1) Residual rate of the coating layer (mass %) = (mass of the coating layer after treatment) / (mass of the coating layer before treatment) × 100

[0128] A coating agent that satisfies the requirements for the residual rate of the coating layer represented by (Formula 1) above preferably contains an aqueous resin and a coloring agent. In this case, the aqueous resin is preferably an aqueous resin having an acidic group. The coloring agent is preferably inorganic fine particles.

[0129] Other embodiments of this disclosure provide a coating agent comprising an aqueous resin and a colorant used in the manufacturing method of the embodiments described above. Details of the aqueous resin and colorant are as described above. [Examples]

[0130] The present disclosure will be described in detail below with reference to examples, but the present disclosure is not limited to these examples. In this disclosure, parts and % refer to parts by mass and mass %, respectively, unless otherwise noted. Also, in the table, NV means non-volatile content.

[0131] <Method for measuring the pH of water extracted from inorganic fine particles> Five parts of inorganic fine particles and 100 parts of deionized water were mixed and heated at 100°C for 5 minutes. After cooling to room temperature, deionized water was added until the total volume of inorganic fine particles and deionized water reached 105 parts. After stirring, the pH was measured using a multi-pH meter (manufactured by AS ONE Corporation) in accordance with JIS Z 8802.

[0132] <Viscosity measurement> The viscosity of the coating agent was measured in accordance with JIS K 7117-1 using a Viscometer TUB-10 manufactured by Toki Sangyo Co., Ltd. under the following conditions. If the non-volatile content concentration was low, the lid of the coating agent storage container was opened and allowed to stand to allow the solvent to evaporate, thereby adjusting the non-volatile content. Measurement conditions • Rotor: M1 • Rotation speed: 6 rpm • Liquid temperature: 25℃ • Non-volatile content when measuring viscosity before dilution: 18% by mass • Non-volatile content when measuring viscosity after dilution: 10% by mass

[0133] <Weight average molecular weight measurement> The weight-average molecular weight was determined as the converted molecular weight using polystyrene as the standard substance. The measuring instrument used was a GPC instrument: Showa Denko Corporation Shodex GPC-401, column: Showa Denko Corporation Shodex OHpak LB-805, and detector: RI (differential refractometer). A 0.1 N NaNO3 aqueous solution was used as the eluent, and the measurement was performed at a column temperature of 35°C and a flow rate of 3 mL / min.

[0134] <Preparation of resin solution> (Preparation example 1) Resin solution V01 Twelve parts of polyvinyl alcohol resin PVA1 and eighty parts of deionized water were heated while stirring at 90°C for one hour. After that, heating was stopped, and stirring was continued until it returned to room temperature to obtain resin solution V01.

[0135] (Preparation Examples 2-6) Resin Solutions V02-06 Resin solutions V02 to V06 were obtained using the same method as in Preparation Example 1, except that the raw materials and mixing ratios listed in Table 1 were changed. The properties of the raw materials used in Preparation Examples 1 to 6 are as follows.

[0136] • Polyvinyl alcohol resin PVA1: Itaconic acid-modified polyvinyl alcohol, degree of polymerization = 1800, viscosity (20℃, 4% aqueous solution) = 25 mPa·s, degree of saponification = 88%, non-volatile content 100% Polyvinyl alcohol resin PVA2: Sulfonic acid modified polyvinyl alcohol, degree of polymerization = 300, viscosity (20℃, 4% aqueous solution) = 2.5 mPa·s, degree of saponification = 98%, non-volatile content 100% Polyvinyl alcohol resin PVA3: Ethylene vinyl alcohol resin, ethylene content: 8 mol%, degree of polymerization = 400, viscosity (20℃, 4% aqueous solution) = 4 mPa·s, degree of saponification = 98%, non-volatile content 100% • Polyvinyl alcohol resin PVA4: Manufactured by Kuraray Co., Ltd., POVAL 28-98, unmodified polyvinyl alcohol, degree of polymerization = 1700, viscosity (20℃, 4% aqueous solution) = 28 mPa·s, degree of saponification = 98%, non-volatile content 100% • Hydroxypropyl cellulose resin: Manufactured by Nippon Soda Co., Ltd., HPC-SL, viscosity (25℃, 10% aqueous solution) = 150 mPa·s, non-volatile content 100% • Pullulan: Manufactured by Nagase Viita, pullulan, 100% non-volatile content. • Styrene-acrylic resin: Hyros X QL-1358 (manufactured by Seikoh PMC, solids content 24.3%, acid value 190 mg KOH / g) • Polyacrylamide resin: Arakawa Chemical Industries, Ltd., Polystrom 705, non-volatile content 10%. • Polyethyleneimine resin: Manufactured by Nippon Shokubai Co., Ltd., Epomin P-1000, non-volatile content 30%.

[0137] (Synthesis Example 1) Synthesis of carboxyl group-containing urethane resin A 2000 ml four-necked flask equipped with a reflux condenser, dropping funnel, gas inlet tube, stirrer, and thermometer was charged with 52.3 parts of polytetramethylene glycol with a number average molecular weight of 2000, 25 parts of polyethylene glycol with a number average molecular weight of 2000, 13 parts of dimethylolbutanoic acid, 8 parts of bis(2-hydroxypropyl)aniline, and 1.7 parts of 1,4-cyclohexanedimethanol. The flask was then purged with dry nitrogen and heated to 100°C. Under stirring, 41.3 parts of isophorone diisocyanate were added dropwise over 20 minutes, and the temperature was gradually increased to 140°C (NCO / 0H = 0.95). After reacting for a further 30 minutes, 750 parts of distilled water containing 8.9 parts of 28% aqueous ammonia were added while cooling to obtain a carboxyl group-containing urethane resin with a non-volatile content of 25% (weight-average molecular weight approximately 40,000, glass transition temperature -91°C, acid value 34.8 mg KOH / g, hydroxyl value = 11.1 mg KOH / g).

[0138] (Synthesis Example 2) Synthesis of Oil-Based Urethane Resin 120.6 parts of ethyl acetate, 153.7 parts of a polyester polyol with a number average molecular weight of 2,000 (hereinafter referred to as "MPD / AdA 2000"), which is a condensate of 3-methyl-1,5-pentanediol (MPD) and adipic acid (AdA), 27.9 parts of a polyester polyol with a number average molecular weight of 5,000 (hereinafter referred to as "MPD / AdA 5000"), which is a condensate of 3-methyl-1,5-pentanediol (MPD) and adipic acid (AdA), 12.4 parts of polypropylene glycol with a number average molecular weight of 700 (hereinafter referred to as "PPG 700"), 35.0 parts of polypropylene glycol with a number average molecular weight of 2,000 (hereinafter referred to as "PPG 2000"), and 52.3 parts of isophorone diisocyanate (hereinafter referred to as "IPDI") were mixed and reacted at 90°C for 5 hours under a nitrogen atmosphere to obtain a urethane prepolymer of terminal isocyanates. Next, 279.6 parts of isopropanol, 299.7 parts of ethyl acetate, 2.1 parts of iminobispropylamine (hereinafter "IBPA"), and 16.6 parts of isophoronediamine (hereinafter "IPDA") were stirred and mixed, and the resulting urethane prepolymer of terminal isocyanates was gradually added at 40°C. The mixture was reacted at 80°C for 1 hour to obtain a solution of oily urethane resin with a non-volatile content of 30% by mass, a urea bond concentration of 0.78 mmol / g, an amine value of 1.3 mg KOH / g, and a mass-average molecular weight of 36100.

[0139] [Table 1]

[0140] <Manufacturing of coating agents> (Manufacturing Example 1) Coating Agent C1 75.0 parts of resin solution V01, 9.0 parts of calcium carbonate, 8.0 parts of deionized water, and 8.0 parts of n-propyl alcohol were mixed and dispersed in a bead mill for 20 minutes to obtain coating agent C1.

[0141] (Manufacturing Examples 2-24, Comparative Manufacturing Examples 1 and 2) Coating agents C2-24, CC1 and CC2 Coating agents C2-24 were obtained using the same method as in Production Example 1, except that the raw materials and mixing ratios listed in Table 2 were changed. The properties of the raw materials used are as follows. The pH is the pH of the extracted water for each.

[0142] • Calcium carbonate CA1: Manufactured by Shiraishi Calcium Co., Ltd., Homocal D, synthetic calcium carbonate, average particle size 0.08 μm, pH 8.6, 100% non-volatile content. Calcium carbonate (CA2): Average particle size 0.3 μm, pH 8 Calcium carbonate (CA3): Average particle size 1.5 μm, pH 9 Calcium carbonate (CA4): Average particle size 4.5 μm, pH 8.9 • Silica: Fuji Silysia Chemical Co., Ltd., Silysia 310, gel-processed silica, average particle size 1.7 μm, pH 7.5 Barium sulfate: Manufactured by Sakai Chemical Industry Co., Ltd., Variace B31, precipitated barium sulfate, average particle size 0.3 μm, pH 7 Montmorillonite: Manufactured by Kunimine Industries Co., Ltd., Kunipia F, swelling montmorillonite, particle aspect ratio 500, particle thickness 1 μm, average particle diameter 0.5 μm, pH 8~8.5 • Carbon Black: Made by Columbia Carbon, Raven 420P • Copper phthalocyanine: Toyo Color Co., Ltd., LIONOL BLUE FG7400-G, Pigment Blue 15:4 • Azo pigment: Manufactured by Toyo Color Co., Ltd., LIONOL RED 5620, Pigment Red 146, insoluble azo pigment • Nigrosine-based black dyes: WATER BLACK R-455, CIAcid BLACK2, manufactured by Orient Chemical Industries Co., Ltd. • Azo dye: Water Black 256L, manufactured by Orient Chemical Industries, Ltd., water-soluble disazo dye

[0143] <Example 1> To coating agent C1, a diluent solvent (water / n-propyl alcohol = 92 / 8) was added so that the non-volatile content of the coating agent was 10%, and the mixture was stirred. A gravure printing press equipped with a gravure plate with a plate depth of 20 μm and fine line stripe patterns of line widths of 20 μm, 50 μm, 100 μm, and 200 μm (cell formation method: etching method, laser plate making device D1: MDC's laser plate making device / electronic engraving machine DIGILAS5000, line count 300 lines / inch, plate depth 20 μm, plate pattern line width / target pattern line width: 90%) was used to print a diluted coating agent C1 onto a PET film (Toyobo Co., Ltd., Cosmoshine A4160, thickness 50 μm) unwound from a printed roll. Under conditions of a printing speed of 150 m / min and an in-line oven of 80°C, a coating layer was formed by printing with a diluted coating agent C1, thereby obtaining a first intermediate laminate having fine line patterns of line widths of 20 μm, 50 μm, 100 μm, and 200 μm. These processes were carried out using a roll-to-roll method.

[0144] On the surface of the first intermediate laminate with a fine line pattern printed using a coating agent, and on a substrate without a pattern, the film was formed at a pressure of 0.37 Pa and an input power density of 3.3 W / cm². 2 The substrate was adjusted, and under the introduction of argon and oxygen gas (argon:oxygen = 95:5), ITO containing 95% by mass of indium oxide and 5% by mass of tin oxide was sputtered to form a conductive film with an average thickness of 0.02 μm, obtaining a second intermediate laminate. This laminate consists of a substrate / coating layer / conductive film component and a substrate / conductive film component, and these processes were carried out using a roll-to-roll method.

[0145] The second intermediate laminate was brought into contact with 40°C water in a cleaning layer for 3 minutes to remove the pattern coating layer and the conductive film located on the pattern coating layer, and then dried by air blowing to obtain a laminate. This laminate has a substrate / conductive film component, and these processes were carried out using a roll-to-roll method.

[0146] <Examples 2-39, 42-67, Comparative Examples 1 and 2> A laminate was prepared in the same manner as in Example 1, except that the coating agent, printing conditions, substrate, conductive film, and cleaning method shown in Table 2 were changed. The substrate used is as follows:

[0147] • Polyimide: Kapton H, manufactured by Toray DuPont, 25 μm thick • PEN: Toyobo Co., Ltd., Theonex Q51, 50 μm thickness

[0148] <Example 40> On a PET film (Toyobo Co., Ltd., Cosmoshine A4160, 50 μm thick) unwound from a printing roll, a flexographic plate (Milacron FLEXCELNXH digital flexographic plate, 1.14 mm thick, 150 lines / inch) with fine line stripe patterns of line widths of 20 μm, 50 μm, 100 μm, and 200 μm was printed, along with an anilox roll (900 lpi 3 cc / m²). 2 Using a flexographic printing press (MIRAFLEXCM) equipped with ), the coating agent C23 was printed under conditions of a printing speed of 150 m / min and an in-line oven at 80°C to form a coating layer, and a first intermediate laminate having fine line patterns with line widths of 20 μm, 50 μm, 100 μm, and 200 μm was obtained. These processes were carried out using a roll-to-roll method. The subsequent conductive film formation process and cleaning process were carried out in the same manner as in Example 1.

[0149] <Example 41> A coating layer was formed on a PET film (Toyobo Co., Ltd., Cosmoshine A4160, 50 μm thick) unwound from a printed roll using a Mitsubishi BT2-800 NEO offset web printing press (Mitsubishi Heavy Industries, Ltd.) equipped with a CTP plate (Toray Industries, Inc., resolution 2000 dots / inch) having fine line stripe patterns with line widths of 20 μm, 50 μm, 100 μm, and 200 μm. The coating agent C24 was printed at a printing speed of 150 m / min and an in-line oven at 80°C to obtain a first intermediate laminate having fine line patterns with line widths of 20 μm, 50 μm, 100 μm, and 200 μm due to the coating agent. These processes were carried out using a roll-to-roll method. The subsequent conductive film formation process and cleaning process were carried out in the same manner as in Example 1.

[0150] <Evaluation of coating agents and laminates> The obtained coating agents and laminates were evaluated as follows. The results are shown in Tables 2 to 4.

[0151] <Suitable for high-speed printing (gravure printing)> For coating agents C1-C22, CC1, and CC2, after dilution with the diluting solvents listed in Table 2, they were poured into the printing ink container of the printing press. Under conditions of a printing speed of 150 m / min for 60 minutes, the colored area of ​​the non-image portion on the plate after rotation was visually evaluated, and the suitability for high-speed printing was assessed according to the following criteria. Grades A-C represent practical levels.

[0152] A: There is no coloring in the non-image areas. B: There is coloring in the non-image area, and the colored area is less than 5% of the total area. C: Non-image areas are colored, with a colored area of ​​5% or more but less than 30%. D: There is coloring in the non-image area, and the colored area is 30% or more.

[0153] <Suitable for high-speed printing (flexographic printing)> After printing with coating blue C23 onto PET film using a flexographic printing press (MIRAFLEXCM), the press was run idle for 30 minutes. After the idle period ended, the PET film was printed again, and the print quality was visually evaluated. Grades A to C represent practical levels.

[0154] A: There are absolutely no printing inconsistencies. B: Slight printing inconsistencies are noticeable. C: Printing inconsistencies are observed. D: Printing inconsistencies are very noticeable.

[0155] <Suitable for high-speed printing (waterless offset printing)> The coating agent C24 was added to the printing ink container of the printing press, and printed onto PET film using a Mitsubishi BT2-800 NEO offset web printing press (manufactured by Mitsubishi Heavy Industries, Ltd.). The degree of background contamination (ink adhesion to non-image areas) was visually evaluated. Grades A to C represent practical levels.

[0156] A: No soiling was observed. B: Slight soiling is visible. C: Some staining is visible on the surface. D: Significant soiling is visible.

[0157] <Stability over time> The coating agent was filled into a 225g mayonnaise jar (body diameter 62mm / total length 109mm), and phase separation was observed after 7 days at 40°C. The following criteria were used for evaluation. The length for each criterion is the length of the layer measured when viewing the mayonnaise jar from the horizontal. Grades A to C represent practical levels.

[0158] A: There is no phase separation. B: Phase separation occurs, and a separation layer less than 10 mm thick is generated. C: Phase separation occurs, resulting in a separation layer between 10mm and 20mm in thickness. D: Phase separation occurs, and a separation layer of 20 mm or more is generated.

[0159] <Fine line reproducibility> The fine-line stripe pattern portion of the resulting laminate was visually observed and evaluated according to the following criteria. AA to C represent practical levels.

[0160] AA: There are no breaks in any of the stripe pattern sections. A: There are breaks in the 20μm fine-line stripe pattern section, but there are no breaks in the 50μm, 100μm, and 200μm fine-line stripe pattern sections. B: There are breaks in the 50μm fine-line stripe pattern section, but there are no breaks in the 100μm fine-line and 200μm fine-line stripe pattern sections. C: There is a break in the 100μm fine line stripe pattern, but there is no break in the 200μm fine line stripe pattern. D: There is a break in the 200μm stripe pattern.

[0161] <Cleaning properties> The residual rate (mass %) of the coating layer before and after cleaning was calculated and evaluated using Equation 1 below, based on the mass of the obtained laminate and the second intermediate laminate before cleaning. AA to C represent practical levels. When the coating agent of this disclosure is used in a lift-off process, in order to achieve high productivity, it is preferable to remove the coating layer only by immersion in water or alkaline water. Therefore, the cleanability test of this disclosure is limited to contact with water or alkaline water. Conventional cleanability tests are known to remove the coating layer by applying pressure with a water flow or the like. However, the immersion cleanability test of this disclosure differs from conventional cleanability tests in that it does not apply pressure with a water flow or the like, and is a rigorous test method that requires higher solubility in the cleaning solution. (Formula 1) Coating layer residue rate (mass %) = (mass of coating layer after cleaning) / (mass of coating layer before cleaning) × 100

[0162] AA: The residual rate (by mass) of the coating layer is less than 5% by mass. A: The residual rate (mass%) of the coating layer is 5% or more and less than 10% by mass. B: The residual rate (mass%) of the coating layer is 10% or more and less than 50% by mass. C: The residual rate (by mass) of the coating layer is 50% by mass or more and less than 80% by mass. D: The residual rate (mass%) of the coating layer is 80% by mass or more.

[0163] <Visibility of thin lines> The visibility of the pattern coating layer on the obtained first intermediate laminate was evaluated visually.

[0164] A: The outline of a 20 μm wide thin line can be seen. B: The outline of a 20 μm wide thin line is not visible, but the outline of a 50 μm wide thin line is visible. C: The outlines of 20 μm and 50 μm wide thin lines are not visible, but the outline of a 100 μm thin line is visible. D: The outlines of 20μm wide, 50μm wide, and 100μm wide lines cannot be seen.

[0165] [Table 2]

[0166] [Table 2]

[0167] [Table 3]

[0168] [Table 3]

[0169] [Table 4]

[0170] While this disclosure has been described with reference to some of the embodiments described above, this disclosure is not limited to those embodiments. Various modifications can be made to the structure and details of this disclosure within the scope of this disclosure. [Explanation of Symbols]

[0171] 1. Substrate, 2. Pattern coating layer, 3. Conductive film, 4. Laminate 10 Substrate supply unit 10, 20 Coating agent printing unit, 30 Conductive film forming unit, 40 Substrate discharge unit 101 Base material rolls 101, 102 Base material 102, 401 Base material rolls after printing

Claims

1. A process of forming a patterned coating layer on a substrate by printing a coating agent containing an aqueous resin and a coloring agent using a roll-to-roll method, without using photolithography. A step of forming a conductive film on a substrate on which the coating layer has been formed using a roll-to-roll method, and A method for manufacturing a laminate, comprising the step of contacting a substrate on which the conductive film is formed with a coating layer removal liquid to remove the coating layer and form a conductive pattern.

2. The method for manufacturing a laminate according to claim 1, wherein the printing is at least one selected from the group consisting of gravure printing, flexographic printing, waterless offset printing, inkjet printing, and screen printing.

3. The method for manufacturing a laminate according to claim 1 or 2, wherein the thickness of the conductive film is 0.01 to 100 μm.

4. A method for manufacturing a laminate according to claim 1 or 2, wherein the thickness of the conductive film and the thickness of the coating layer satisfy the following formula. Equation 1: Thickness of conductive film [μm] < Thickness of coating layer [μm]

5. The method for producing a laminate according to claim 1 or 2, wherein the coloring agent comprises at least one selected from the group consisting of organic pigments, inorganic pigments, and dyes.

6. The method for producing a laminate according to claim 1 or 2, wherein the aqueous resin contained in the coating agent includes an aqueous resin having a polar structure.

7. The method for producing a laminate according to claim 1 or 2, wherein the coating layer removal liquid is water or an alkaline aqueous solution.

8. A coating agent comprising an aqueous resin and a colorant used in the manufacturing method described in claim 1 or 2.

Citation Information

Patent Citations

  • Method for patterning metallic oxide film

    JP2002200833A

  • Method of manufacturing touch panel substrate

    JP2013257669A

  • Resist agent for lift-off technique and manufacturing method of conductor pattern

    JP2013258215A